Strong cation exchange (SCX) based analytical methods for the targeted analysis of protein post-translational modifications. - Mohammed, S; Heck, A (2011)
The multidimensional combination of strong cation exchange (SCX) chromatography and reversed phase chromatography has emerged as a powerful approach to separate peptides originating from complex samples such as digested cellular lysates or tissues before analysis by mass spectrometry, enabling the identification of over 10,000s of peptides and thousands of proteins in a single sample. Although, such multidimensional chromatography approaches are powerful, the in-depth analysis of protein post-translational modifications still requires additional sample preparation steps, involving the specific enrichment of peptides displaying the targeted modification. Here, we describe how in particular SCX chromatography can be used for the targeted analysis of important post-translational modifications, such as phosphorylation and N-terminal acetylation. Compared to other methods, SCX is less labor-intensive and more robust, and therefore likely more easily adaptable to main-stream research laboratories.